LEARNING GUITAR MUSIC SKILLS THROUGH THE DEMONSTRATION METHOD AT STATE SENIOR HIGH SCHOOL 1 LAMONGAN - sultan daffa islami akbar, sultan; murbiyantoro, heri (Solah, 2026)
Music instruction at SMA Negeri 1 Lamongan aims to improve guitar playing skills and foster a sense of artistry through the development and awareness of the importance of music in life. Music can also be a medium for expressing students' identities and developing their sensitivity to the world around them. Playing music, especially the guitar, is not easy; therefore, a learning method is needed so that students can easily master the skills. One method that teachers can use to improve music playing skills is the demonstration method through video media. The demonstration method is a presentation of lessons by demonstrating or showing students through a process, situation, or certain objects being studied, either real or imitation, which is often accompanied by oral explanations. It is hoped that with the help of the demonstration method, improving guitar playing skills will be fun for students, especially class X. The video-assisted demonstration method shows positive results, where students' abilities in playing music with the guitar have increased. The proof is that students can strum the guitar and press the strings correctly, students can play chords according to the teacher's assignment. So it can be concluded that video as a visual aid media has proven effective in providing concrete images and attracting interest in learning, in addition to making learning more interactive and enjoyable.